Analysis of the alkali-activated fly ashes from electrostatic precipitators by impedance measurements. (November 2019) - Walter, J; Mierzwiński, D; Kosiba, K
Abstract: Curing the fly ash materials with addition of sand activated by 8 M sodium hydroxide (NaOH) was analysed by impedance spectroscopy. The measurements were carried out for 6 hours from the moment the samples were put into the oven at 75 °C. It was found characteristic similar shape of impedance curves recorded versus time of solidification process. Starting from the curve obtained after 52 min to longer times impedance curve crossed at about 30 Hz. The first lower than 30 Hz frequencies range showed continues decreasing of impedance values with increasing the time. Changes in impedance curve versus time looks different for second frequencies higher than 30 Hz. Temperature of the material increases slightly over temperature of the oven as a result of exothermic reactions which can be seen at impedance vs. time curve as a bulge. The starting of these reactions can be seen more precisely in the second range of the frequency as a continuous increase of impedance value preceded by its initial fast decline. The main purpose of the article is the possibility of using the described method, it can be particularly useful for assessing the starting point of an exothermic reaction and its progress in the case of different masses of heated material.